Determinants of Financing Risk Level of Islamic Commercial Banks in Indonesia - Indriani , Selfia; Nurmalia , Gustika; Ridha Putri, Previta (Tazkia Islamic University College, 2023)
Financing is an activity of Islamic banks in distributing funds to other parties. Every financing carried out by a bank always contains a risk. The risks faced by Islamic banks are diverse and complex in line with the innovations in the financial and banking products they offer to the public. Although Islamic banks have quite fundamental factors to withstand the occurrence of financing risk, this risk can interfere with the performance of Islamic banking if it is not handled seriously. During the last four years, from the Islamic banking statistics released by the OJK, it is noted that the financing risk that occurs in Islamic Commercial Banks has increased quite significantly. This research is a type of quantitative research. The sampling technique used is purposive sampling. The data processed is secondary data from the annual published reports of Islamic Commercial Banks on the official website of each bank. The data analysis method used in this research is panel data regression analysis with the Eviews 8.0 software in analyzing data. The results obtained from this study indicate that partially UMKM financing, Return In Asset (ROA) has no significant effect on the Financing Risk (NPF) of Islamic Commercial Banks while the Finance to Deposit Ratio (FDR) has a positive and significant effect on the Financing Risk (NPF) of the Bank. Sharia General.